The Involvement of Lactosylceramide in Central Nervous System Inflammation Related to Neurodegenerative Disease - Yu, Wen; Ying, Jun; Wang, Xifeng; Liu, Xing; Zhao, Tiancheng; Yoon, Sungtae; Zheng, Qingcui; Fang, Yang; Yang, Danying; Hua, Fuzhou (Frontiers in Aging Neuroscience, 2021)
Neurodegenerative diseases are a class of slow-progressing terminal illnesses characterized by neuronal lesions, such as multiple sclerosis [MS, Alzheimer’s disease (AD), Parkinson’s disease (PD), and amyotrophic lateral sclerosis (ALS)]. Their incidence increases with age, and the associated burden on families and society will become increasingly more prominent with aging of the general population. In recent years, there is growing studies have shown that lactosylceramide (LacCer) plays a crucial role in the progression of neurodegeneration, although these diseases have different pathogenic mechanisms and etiological characteristics. Based on latest research progress, this study expounds the pathogenic role of LacCer in driving central nervous system (CNS) inflammation, as well as the role of membrane microstructure domain (lipid rafts) and metabolite gangliosides, and discusses in detail their links with the pathogenesis of neurodegenerative diseases, with a view to providing new strategies and ideas for the study of pathological mechanisms and drug development for neurodegenerative diseases in the future.